2019
DOI: 10.2478/raon-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

MRI prognostic factors of tongue cancer: potential predictors of cervical lymph nodes metastases

Abstract: Background This study aimed to evaluate the efficacy of three MR imaging parameters, which are tumour thickness, para-lingual distance and apparent diffusion coefficient (ADC) value for prediction of cervical lymph nodes metastasis in cancer tongue patients. Patients and methods Fifty patients with proved cancer tongue by histopathological examination underwent MRI examination. T1 and T2- weighted MRI, diffusion-weighted images and post-contrast T1 fat suppression sequences were used. Results The patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…In agreement with the findings from previous studies on tongue cancer and HNSCC, we found that the pre-treatment ADC value of the tumor was not an important predictor of recurrence [ 20 , 21 ]. However, our findings were not supported by other studies which showed a statistically significant correlation between pre-treatment ADC value of HNSCC and poor prognosis [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the findings from previous studies on tongue cancer and HNSCC, we found that the pre-treatment ADC value of the tumor was not an important predictor of recurrence [ 20 , 21 ]. However, our findings were not supported by other studies which showed a statistically significant correlation between pre-treatment ADC value of HNSCC and poor prognosis [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is not surprising because the deep invading tumors are closer to deep lymphatics and blood vessels, and thus spread to regional lymph nodes [ 31 ]. We found the optimal cut-off values for tumor thickness were greater than 12.8 mm, which was close to the best cutoff values observed in another study [ 20 ]. High LNR were also reported to be associated with poor survival and high disease recurrence rates in tongue cancer [ 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the location of the tumour, the greater tendency of tumours located at the base of the tongue to metastasize could be related to their anatomical characteristics, such as their vascularization and the proximity to the cervical lymph nodes [63,64]. Therefore, depth of invasion is an important prognostic factor [65].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the parameter of depth of invasion was established as a predictor of the presence of lymph node metastases [48][49][50] and was added as a T-category modifier to the 8th edition of the American Joint Committee on Cancer criteria in 2017 [51][52][53]. Several studies have investigated the ability of diagnostic imaging to evaluate tumor dimensions [54][55][56]; a recent systematic review compared the diagnostic accuracy of magnetic resonance, computed tomography, and ultrasonography in assessing tumor dimensions preoperatively [57]. For magnetic resonance, the sensitivity was >80% and the specificity was >75% in all the studies included in the review, while computed tomography was reported in one study to have a sensitivity of 68.75% and a specificity of 77.78%.…”
Section: Oral Medicinementioning
confidence: 99%